Development of a numerical method for determination of stress intensity factor into the members with cracks - Астанін, В.В.; Бородачов, М.М.; Богдан, С.Ю. (Proceedings of National Aviation University (archive), 2010)
The linear fracture mechanics methods were applied for implementation a principle called safe damage. The problem of stress intensity coefficients determination was considered and a numerical method for their calculation was proposed. An application of the method for structure members with damages and cracks was shown. The analysis of stress-strain states for plates and strips with cracks were fulfilled. The values of stress intensity coefficients К1 for bodies in different configuration were determined based on solution of proper boundary problems and comparison obtained results with known solutions was carried out. Several options of points location at determination displacements fields on crack surface were analyzed.